An Incomplete Death: Artificial Hydration/Nutrition and the PVS Patient - Conn, Marie A. (Theology today, 2019)
The 2004 statement of the late Pope John Paul II, "Care for Patients in a 'Permanent' Vegetative State," highlighted the need to review the Catholic moral tradition concerning artificial hydration and nutrition (AHN). This article will begin with a brief look at the two broad strains of natural law theory as they are reflected in papal and episcopal documents. Other concerns raised by the pope's statement include the traditional distinction between ordinary and extraordinary means; the neurological evaluation of patients in the persistent vegetative state (PVS); the pope's insistence on AHN as a natural and not a medical act; and a more precise evaluation of euthanasia.